The management philosophy of state professional education schools in the state of Ceará-Brazil - Maia, Diego Azevedo; Pinto, Maria Claudeniza Maia; Alves, Sandra Maria Campos (Revista Hipótese, 2019)
The present article aims to present the management philosophy of State Professional Education Schools in the State of Ceará-Brazil, named TESE - Entrepreneurial Socio Educational Technology. Firstly, a discussion based on a bibliographical review is performed, taking into account the trajectory of school management in Brazil. Secondly, we highlight the aspects between school administration and business administration as well as the changes from the concept of administration to management. Finally, TESE exposes the results by considering its characteristics and premises that combine elements of business management with pedagogical management focusing on integral human formation at educational institutions.